2014
DOI: 10.1186/2045-8118-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood–brain barrier permeability and alterations in perivascular astrocytes and pericytes induced by intracisternal glutaric acid

Abstract: BackgroundGlutaric acid (GA) is a dicarboxylic acid that accumulates in millimolar concentrations in glutaric acidemia I (GA-I), an inherited neurometabolic childhood disease characterized by extensive neurodegeneration. Vascular dysfunction is a common and early pathological feature in GA-I, although the underlying mechanisms remain unknown. In the present study, we have used a previously-validated rat model of GA-I to determine the effect of GA on the blood- brain barrier (BBB) and the neurovascular unit.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Transmission electron microscopy showed that striatal OLs from rats injected with GA had endoplasmic reticulum (ER) with significant swollen vesicles indicating significant ER stress. Abnormal myelin sheaths and thinner axons were also consistently found in GAI injected animals [35], all resembling the progressive myelin alterations reported in GAI patients [23,51]. Interestingly, GAI induced myelination failure was restricted to the basal ganglia, the most vulnerable brain area in GAI patients [19,20,23].…”
Section: Astrocytes As Targets For Glutaric Acid and Related Metabolitessupporting
confidence: 63%
See 3 more Smart Citations
“…Transmission electron microscopy showed that striatal OLs from rats injected with GA had endoplasmic reticulum (ER) with significant swollen vesicles indicating significant ER stress. Abnormal myelin sheaths and thinner axons were also consistently found in GAI injected animals [35], all resembling the progressive myelin alterations reported in GAI patients [23,51]. Interestingly, GAI induced myelination failure was restricted to the basal ganglia, the most vulnerable brain area in GAI patients [19,20,23].…”
Section: Astrocytes As Targets For Glutaric Acid and Related Metabolitessupporting
confidence: 63%
“…Interestingly, EB extravasation through the BBB was internalized in striatal neurons but not in astrocytes or microglial cells. This suggests concurrent membrane anomalies in damaged striatal neurons allowing passive entrance of the dye [35].…”
Section: Astrocytes As Targets For Glutaric Acid and Related Metabolitesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it should be stressed that bioenergetics disruption is capable of inducing secondary excitotoxicity (Danbolt, 2001;Novelli et al, 1988). Therefore, it is conceivable that moderate disturbance of bioenergetics, associated with excitotoxicity (Kolker et al, 2002b;Lagranha et al, 2014;Wajner et al, 2004), oxidative stress Seminotti et al, 2012Seminotti et al, , 2013 and increased blood-brain barrier permeability (Isasi et al, 2014;Zinnanti et al, 2014) may contribute to the brain injury in GA I.…”
Section: Discussionmentioning
confidence: 97%